Bruton’s Tyrosine Kinase: An Emerging Key Player in Innate Immunity - Weber, Alexander N. R.; Bittner, Zsofia; Liu, Xiao; Dang, Truong-Minh; Radsak, Markus Philipp; Brunner, Cornelia (Frontiers in Immunology, 2017)
Bruton’s Tyrosine kinase (BTK) was initially discovered as a critical mediator of B cell receptor signaling in the development and functioning of adaptive immunity. Growing evidence also suggests multiple roles for BTK in mononuclear cells of the innate immune system, especially in dendritic cells (DC) and macrophages. For example, BTK has been shown to function in Toll-like receptor-mediated recognition of infectious agents, cellular maturation and recruitment processes, and Fc receptor signaling. Most recently, BTK was additionally identified as a direct regulator of a key innate inflammatory machinery, the NLRP3 inflammasome. BTK has thus attracted interest not only for gaining a more thorough basic understanding of the human innate immune system but also as a target to therapeutically modulate innate immunity. We here review the latest developments on the role of BTK in mononuclear innate immune cells in mouse versus man, with specific emphasis on the sensing of infectious agents and the induction of inflammation. Therapeutic implications for modulating innate immunity and critical open questions are also discussed.